Application of atmospheric pressure cold plasma activated plant protein preparations solutions as an alternative curing method for pork sausages. (May 2022) - Marcinkowska-Lesiak, Monika; Wojtasik-Kalinowska, Iwona; Onopiuk, Anna; Stelmasiak, Adrian; Wierzbicka, Agnieszka; Poltorak, Andrzej
Abstract: This study was performed to determine the effect of plasma-activated solutions of protein preparations of selected plants, as an alternative nitrite source, on the quality characteristics of pork sausages. The used solutions contained 500 ppm nitrite. Sausages without nitrite (NC), with 75 ppm sodium nitrite (PC), and with solutions of soy (E1 ), pea (E2 ) and lentil (E3 ) preparations (100 g/kg of meat ingredients) were manufactured and stored for 8 days. The results showed that after processing sausages from E1, E2 and E3 groups showed similar nitrite content as PC group (20.69–21.89 mg nitrite/kg; P ≥ 0.05). Performed analyses (residual nitrite, nitrosylhemochrome content, a* values, thiobarbituric acid reactive substances, total aerobic plate count) suggested also that addition of nitrite through solutions of soy and pea plasma-activated preparations extended the shelf life of sausages comparable to sodium nitrite without a negative effect on aroma (PCA), as was reported for some other sources of nitrite.